(untitled) (Research Announcements "Heritage BG", 2025)
The article draws attention to understanding apitherapeutic heritage and the opportunity to include honey and bee products in prevention practice and therapy activity, as well as to the prospects for development of wellness education in this country. Characteristics of some of the main bee products and methods of their application are presented. Digitally presented innovations and good honey practices in the Bulgarian certified SPA and Wellness Centers and the Sofia massage studios were analyzed. References: Filonov 2015: Filonov, Sergei. Lechenie na organizma sas sobstveni sili. Sofia. Goranova et al. 2000: Goranova, Zoya, Markova-Stareishinska, Gergina, Kraidjikova, Leila. Masaj. NSA. Sofia. Harnish 2001: Harnish, Gunther. Lecheben masaj s pchelen med. Ed. Akvarius, Sofia. Lisovski 2009: Lisovski, Petar. Prochistvane i podmladyavane. ISBN: 978-954-792-278-5. Sofia. Mladenov 1989: Mladenov, Stoimir. Pchelni produkti – hrana i lekarstvo. Sofia. Pochinkova 1986: Pochinkova, Pavlina. Bees products in medicine. Izdatelstvo na Balgarskata akademia na naukite. Sofia. Tomova 2022: Tomova, Tatyana. Traditions and innovations in the manual impacts in Recreation and Wellbeing. Lecheben massaj pri celulit. – NAUCHNI IZVESTIA – BYULETIN „NASLEDSTVO BG“, ed. Emmanuel Moutafov, 2/2022, Godina II, broy 3, ISSN (Print): 2815-3138 // ISSN (Online): 2815-3316, 88 – 93. Vassilev: 1990, Vassilev, Vasil. Savremenno sastoyanie i perespektivi na apiterapiyata. In: Sbornik s dokladi ot Parva nauchna konferencia po apiterapia. Sofia, 8 – 11. Rossi 2000: Rossi, Ana Beatris R. Cellulite: A Review. Journal of the European Academy of Dermatology and Venereology, No 14 (4), 251-262. DOI: 10.1046/j.1468-3083.2000.00016.x.